Legal Certainty in The Validity of Interfaith Marriages Performed Abroad - Asih, Nur; Uwiyono, A.; Wulandari, Wahyuni Retno (Future Science, 2024)
This research examines in more depth how legal certainty regarding the validity of marriage certificates of different religions is held abroad after being recorded and reported to the Population and Civil Registry Office (Dukcapil), where the couple resides upon returning to the homeland. With lex loci celebrationis and lex fori principles, the state is expected to accept, recognize, and respect as the basis for recording and registration with the Dukcapil. This type of research is normative research using a statutory and factual approach. The data collection method used literature study, field research, and interviews. Based on the results and discussion of the research, it is found that Indonesian Citizens (WNI) who enter into marriages of different religions abroad under International Civil Law (HPI) are valid and recognized. However, when viewed from the applicable marriage law in Indonesia, it is invalid because it still has to be based on religious law. However, sociologically, the community still recognizes and accepts the existence of interfaith marriages.